2014
DOI: 10.1111/and.12221
|View full text |Cite
|
Sign up to set email alerts
|

Reduced testosterone production in TM3 Leydig cells treated withAspalathus linearis(Rooibos) orCamellia sinensis(tea)

Abstract: Flavonoids are major compounds of Aspalathus linearis and Camellia sinensis. They are classified as endocrine disruptors and some have been shown to inhibit testosterone production. TM3 Leydig cell cultures were treated with 250-5000 μg mL(-1) A. linearis (unfermented or fermented rooibos) or Camellia sinensis (green or black tea) for 24 h in the absence or presence of 6 mIU/200 μl human chorionic gonadotropin (hCG). Under nonstimulated conditions, all teas tend to decrease testosterone production (3.9-31.8%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Several earlier studies applied MA-10 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], BLTK1 [ 20 , 35 ], or TM3 cells [ 48 , 49 , 50 , 51 ] to analyze effects of endogenous and exogenous substances on steroidogenesis by measuring T production using antibody-based methods. In most of these studies there is only limited information available on the specificity of the antibody used, and the commercial suppliers mostly included only a limited number of steroid metabolites in their characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies applied MA-10 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], BLTK1 [ 20 , 35 ], or TM3 cells [ 48 , 49 , 50 , 51 ] to analyze effects of endogenous and exogenous substances on steroidogenesis by measuring T production using antibody-based methods. In most of these studies there is only limited information available on the specificity of the antibody used, and the commercial suppliers mostly included only a limited number of steroid metabolites in their characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extract of black tea (2% and 5%) was prepared as previously described by Opuwari and Monsees, (2015).…”
Section: Preparation Of Black Tea Aqueous Extractmentioning
confidence: 99%
“…To validate this claim, Ratnasooriya and Fernando (2008) showed that oral administration of black tea to male Wistar rats enhanced aphrodisiac activity (prolonged latency of ejaculation, decreased mounting and intromission latencies, with increased level of serum testosterone). On the contrary, treatment of TM3 Leydig cells with black tea (250, 500, 1,000 and 5,000 µg/ml) for 24 hr in vitro resulted in a significant decline in testosterone level (Opuwari & Monsees, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rooibos extracts showed positive effects on sperm concentration, viability, and the percentage of motile sperm [ 12 , 13 ]. On the other hand, Opuwari and Monsees [ 14 ] demonstrated that rooibos aqueous extracts possess anti-androgenic properties when were added to TM3 Leydig cells from immature mice testes. Until now, there are no studies about the in vitro effects of rooibos extract on sperm function.…”
Section: Introductionmentioning
confidence: 99%